Genome-wide phylogenetic analysis and expansion of gene families involved in detoxification in Smittia aterrima (Meigen)and Smittia pratorum (Goetghebuer) (Diptera, Chironomidae) - Bin Mao; Yue Zheng; Yunli Xiao; Kaixia Yang; Jingru Shangguan; Mi Shen; Hao Sun; Xiangliang Fang; Yue Fu (BMC Genomic Data)
Abstract Smittia aterrima (Meigen, 1818) and Smittia pratorum (Goetghebuer, 1927) are important indicator insects for aquatic environments, showing extensive tolerance to the environment. However, the genome-wide phylogenetic relationships and characteristics of the detoxification mechanisms in S. aterrima and S. pratorum remain unclear. Based on the genomes of the two species obtained in our preliminary studies and nine genomes from the NCBI database, we found that chironomids diverged from other mosquitoes approximately 200 million years ago (MYA), and S. aterrima and S. pratorum diverged about 30 MYA according to phylogenetic analysis. Gene family evolution analysis showed significant expansion of 43 and 15 gene families in S. aterrima and S. pratorum, respectively, particularly those related to detoxification pathways. Positive selection analysis reveals that genes under positive selection are crucial for promoting environmental adaptation. Additionally, the detoxification-associated gene families including Cytochrome P450 (CYP), Glutathione S-transferases (GST), ATP-binding cassette (ABC), carboxylesterase (CCE), and UDP-glucuronosyltransferase (UGT) were annotated. Our analysis results show that these five detoxification gene families have significantly expanded in the chironomid genomes. This study highlights the genome evolution of chironomids and their responses to mechanisms of tolerance to environmental challenges.